2023
DOI: 10.3802/jgo.2023.34.e58
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effect of fenbendazole-incorporated PLGA nanoparticles in ovarian cancer

Abstract: Objective Fenbendazole (FZ) has potential anti-cancer effects, but its poor water solubility limits its use for cancer therapy. In this study, we investigated the anti-cancer effect of FZ with different drug delivery methods on epithelial ovarian cancer (EOC) in both in vitro and in vivo models. Methods EOC cell lines were treated with FZ and cell proliferation was assessed. The effect of FZ on tumor growth in cell line xenograft mouse model of EOC was examined accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Another group attempted the delivery of fenbendazole (antihelminthic drug) to epithelial ovarian cancer via PLGA nanoparticles (FZ-PLGA-NPs). 48 The FZ-PLGA-NPs significantly decreased cell proliferation and reduced tumor weight compared with the control groups. Furthermore, as-synthesized PLGA nanoparticles have been coloaded with macrolide compound rapamycin and piperine (alkaloid) to treat multi drug resistant (MDR) breast cancer.…”
Section: Drug Deliverymentioning
confidence: 88%
See 1 more Smart Citation
“…Another group attempted the delivery of fenbendazole (antihelminthic drug) to epithelial ovarian cancer via PLGA nanoparticles (FZ-PLGA-NPs). 48 The FZ-PLGA-NPs significantly decreased cell proliferation and reduced tumor weight compared with the control groups. Furthermore, as-synthesized PLGA nanoparticles have been coloaded with macrolide compound rapamycin and piperine (alkaloid) to treat multi drug resistant (MDR) breast cancer.…”
Section: Drug Deliverymentioning
confidence: 88%
“…Tumor cell proliferation was inhibited following treatment, while there was reversion of immunosuppressive tumor microenvironment (TME). Another group attempted the delivery of fenbendazole (antihelminthic drug) to epithelial ovarian cancer via PLGA nanoparticles (FZ-PLGA-NPs) . The FZ-PLGA-NPs significantly decreased cell proliferation and reduced tumor weight compared with the control groups.…”
Section: Polymeric Platformsmentioning
confidence: 99%
“…In vitro observations do not always reflect in vivo immune responses. Previous in vivo studies have reported the anticancer effects of FBZ in SCID [25] and nude mice [22,28,29]. A study using mice with normal immunity reported no anticancer effects of FBZ [24,26].…”
Section: Discussionmentioning
confidence: 99%
“… 427 In other studies, Chi-Son Chang and colleagues reported that fenbendazole-incorporated PLGA nanoparticles exerted significant anticancer effects in epithelial ovarian cancer cells and xenograft models, including patient-derived xenografts (PDX). 428 PLGA has also been involved in preclinical studies for combination therapy. One study justifies additional preclinical safety trials and the clinical evaluation of 177Lu-PLGA(RGF)-CXCR4L as a potential combined treatment for colorectal cancer.…”
Section: Nanomedicinementioning
confidence: 99%